How to make a revolution: the historical and political writings of Raymond Postgate - Mulholland, M (Lawrence and Wishart, 2016)
I came across the work Raymond Postgate (1896-1971) because he wrote about the kinds of things I am interested in: labour history, the history of the left, revolutions, and Ireland. What I found particularly attractive, however, was his writing style. Postgate was a skilled journalist and editor. He knew how to grab the reader. This is evident in the large survey history he wrote with GDH Cole in 1938, The Common People. The first pages of this book, in which Postgate depicts the final destruction of the old world with the defeat of the clans at Culluden, is a masterpiece of evocation and drama. Following on hard is a tour of Great Britain mapping out the social and economic conditions of the people in 1750. Here the hand of GDH Cole is evident. One feels it would be less laborious to undertake the journey by foot. The Common People is often discussed as though Cole wrote the substance while Postgate applied the decoration. Certainly Postgate added much of the style that made it a bestseller, but his analysis is evident throughout.